2016
DOI: 10.1590/2179-8087.104914
|View full text |Cite
|
Sign up to set email alerts
|

Análise Econômica e de Sensibilidade em um Povoamento Implantado no Sudoeste da Bahia

Abstract: RESUMOA execução de um projeto florestal deve ser norteada por ferramentas de análise econômica, de forma que se possa respaldar os investimentos realizados. Objetivou-se neste trabalho promover uma análise econômica e de sensibilidade em projetos de reflorestamento de eucalipto na microrregião de Vitória da Conquista, BA. Utilizou-se como critério o Valor Presente Líquido, a Taxa Interna de Retorno, o Valor Periódico Equivalente e o Custo Médio de Produção. A análise de sensibilidade foi realizada através da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 5 publications
0
11
0
13
Order By: Relevance
“…The cost of eucalyptus seedlings at planting and replanting was 14.63% of the implementation cost of a reforestation area in Bahia state, according to Virgens et al (2016). Vasconcelos et al (2012) analyzed the costs of four forestry nurseries and concluded that the effective cost management is important for the success of the venture, which demands accurate cost control as well as investment plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of eucalyptus seedlings at planting and replanting was 14.63% of the implementation cost of a reforestation area in Bahia state, according to Virgens et al (2016). Vasconcelos et al (2012) analyzed the costs of four forestry nurseries and concluded that the effective cost management is important for the success of the venture, which demands accurate cost control as well as investment plans.…”
Section: Introductionmentioning
confidence: 99%
“…Within forestry area, Sant' Anna & Leonel (2009) and Virgens et al (2016) advise the use of tools which consider the variation of capital along time, such as Net Present Value (NPV), Internal Return Rate (IRR) and Equivalent Uniform Annual Cost (EUAC). Furthermore, it can also be considered Benefit/Cost Ratio (B/C R) (Rezende & Oliveira, 2008), Breakeven Point (BEP) and Equivalent Uniform Annual Value (EUAV) (Silva & Fontes, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…O VPL exibiu um valor de R$ 49.736,30 onde foi atribuída uma taxa de juros 6,75 % que corresponde ao custo médio por hectare da produção do eucalipto. Esse valor foi superior ao VPL (R$ 12.790,01 ha 1 ) obtido por Virgens et al (2015) ao avaliarem a viabilidade econômica de projetos de reflorestamentos com clones de eucalipto no estado da Bahia, tal resultado pode ser explicado pelo espaçamento utilizado no presente trabalho, onde foi cultivado um número maior de árvores (555 plantas) por ha, proporcionando maior produtividade e consequentemente maior retorno econômico.…”
Section: Resultsunclassified
“…Além do espaçamento adequado, a execução de um projeto de reflorestamento deve ser norteado por meio de ferramentas de análise financeira e econômica, a fim de respaldar os investimentos realizados (VIRGENS et al, 2016).…”
Section: Introductionunclassified